Professional Ethics Standards and Trust in Financial Reporting Systems (gjstudies, 2025)
This research investigates the underexplored intersection of formalized professional ethicsstandards and the computational trust mechanisms within automated financial reportingsystems. While extensive literature exists on ethics in accounting and on technical trustin information systems, a significant gap persists regarding how codified ethical principles—specifically those mandated by professional bodies like the AICPA and IFAC—canbe operationalized as explicit, measurable inputs to enhance the perceived and actual reliability of algorithmic financial reporting platforms. Current approaches to trust in financialtechnology often focus on cryptographic security, audit trails, or data integrity checks, treating ethical considerations as an external, human-centric overlay rather than an embeddedsystem attribute. This paper posits a novel methodology: the Ethical Trust Quantification(ETQ) framework, which translates discrete provisions from major professional ethics codes(e.g., integrity, objectivity, professional competence, confidentiality) into quantifiable metrics that can influence system behavior, user interface design, and transparency reporting.Through a mixed-methods approach involving a simulated financial reporting environment,we model how the explicit integration of ETQ metrics affects stakeholder trust perceptionsamong three distinct groups: auditors, financial analysts, and institutional investors. Ourresults, derived from controlled experiments and survey data, indicate that systems featuringvisible, ethics-based trust indicators elicit a 34.7% higher mean trust score compared to systems with identical technical robustness but without explicit ethical signaling. Furthermore,the research identifies a previously unreported moderating effect: the impact of embeddedethics signaling is most pronounced in scenarios involving complex, judgment-based financialestimates rather than routine transactional reporting. The study concludes that the formalization and system-level integration of professional ethics standards represent a critical, yetlargely untapped, lever for building trust in increasingly autonomous financial ecosystems.This cross-disciplinary contribution bridges accounting ethics, human-computer interaction,and trustworthy AI, proposing a concrete path to harden the socio-technical fabric of financial reporting.